Molecular diversity of peanut-nodulating rhizobia in soils of Argentina - Bogino, Pablo Cesar (2010)
RSα sequencing is a valuable tool for identification of bacterial strains, and for evaluating the genetic structure of indigenous rhizobial populations. The purpose of this study was to evaluate, qualitatively, the presence or absence of RSα fragment in peanut‐nodulating strains isolated from plants grown at four sites in central Argentina. RSα fragment was found in only three of 26 indigenous strains, and in one of three inoculant strains analyzed. In contrast to results from studies of other symbiotic nitrogen‐fixing bacteria, such as soybean‐nodulating strains, no correlation was found between generation time and presence of RSα sequence. Phylogenetic analysis of the 16S rRNA gene sequence grouped peanut‐nodulating strains into two clusters, Bradyrhizobium japonicum vs. B. elkanii, and showed divergence among strains positive for RSα sequence. Our results confirm the genetic diversity previously reported for various peanut‐nodulating rhizobial strains, and indicate that the RSα fragment is not applicable as a marker or tool for competition assays at the field or ecological level.